Engineering human stellate cells for beta cell replacement therapy promotes in vivo recruitment of regulatory T cells. (March 2019) - Oran, D.C.; Lokumcu, T.; Inceoglu, Y.; Akolpoglu, M.B.; Albayrak, O.; Bal, T.; Kurtoglu, M.; Erkan, M.; Can, F.; Bagci-Onder, T.; Kizilel, S.
Abstract: Type 1 diabetes (T1D) is an autoimmune disease characterized by destruction of pancreatic β cells. One of the promising therapeutic approaches in T1D is the transplantation of islets; however, it has serious limitations. To address these limitations, immunotherapeutic strategies have focused on restoring immunologic tolerance, preventing transplanted cell destruction by patients' own immune system. Macrophage-derived chemokines such as chemokine-ligand-22 (CCL22) can be utilized for regulatory T cell (Treg) recruitment and graft tolerance. Stellate cells (SCs) have various immunomodulatory functions: recruitment of Tregs and induction of T-cell apoptosis. Here, we designed a unique immune-privileged microenvironment around implantable islets through overexpression of CCL22 proteins by SCs. We prepared pseudoislets with insulin-secreting mouse insulinoma-6 (MIN6) cells and human SCs as a model to mimic naive islet morphology. Our results demonstrated that transduced SCs can secrete CCL22 and recruit Tregs toward ​the implantation site in vivo . This study is promising to provide a fundamental understanding of SC-islet interaction and ligand synthesis and transport from SCs at the graft site for ensuring local immune tolerance. Our results also establish a new paradigm for creating tolerable grafts for other chronic diseases such as diabetes, anemia, and central nervous system (CNS) diseases, and advance the science of graft tolerance. Graphical abstract: Engineering human stellate cells for beta cell replacement therapy promotes in vivo recruitment of regulatory T cells (Tregs). Image 1